The Effect of Social Media and Brand Image on Wardah Liquid Lipstick Consumer’s Repurchase Intention in Malang City - Dzikrillah Khoirun Nisa; Ratih Juliati; Novi Puji Lestari (Jamanika (Jurnal Manajemen Bisnis dan Kewirausahaan), 2023)
This study aims to examine and analyze the effect of social media and brand image on repurchase intention. The population in this study is Wardah liquid lipstick consumers. This study uses a non-probability sampling technique with purposive sampling and quota sampling methods. Data collection techniques using online questionnaires via Google form. The analysis tool uses SPSS 25. The results showed that social media had a positive and significant effect on repurchase intentions, the brand image had a positive and significant effect on repurchase intentions, and social media had a dominant influence on repurchase intentions.